PENERAPAN MODEL PEMBELAJARAN KOOPERATIF TIPE THINK PAIR SHARE (TPS) UNTUK MENINGKATKAN HASIL BELAJAR MATEMATIKA SISWA KELAS IV C SD NEGERI 80 PEKANBARU - Rakhmawati, Rakhmawati; Antosa, Zariul; Munjiatun, Munjiatun (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2016)
Abstract: The background of this research was low study result in mathematics. This might be caused on teaching method. The teachers use speaking method and text book only from the source. The type of Cooperative learning method â€žthink Pair Shareâ€ can increase the study result of mathematics on SDN 80 Pekanbaru students of fourth graders. The subject of this research was 36 persons of C fourth graders students of SDN 80 Pekanbaru 2014/2015 . This research has been used by Class Proceed Research that be done by 2 cycles, each cycle has been done in twice of meetings within once final post test. This activity aims to increase the learning result of C class fourth graders of SDN 80 Pekanbaru on mathematics. The result of this research shows that the type of cooperative learning method â€œthink pair shareâ€ can increase study result of C fourth graders students of SDN 80 Pekanbaru on mathematics. The initial data is obtained that study result average increases from 68,19 became 76,11 on first daily post test, its show increasing study result from base score to first post test at 11,61%. Furthermore, at second cycle was obtained that study result increase from base score to second cycle post test at 22,20% with base score average was 68,19% increase became 83,33% at second daily post test. According to above explanation can be concluded that cooperative learning method â€œThink Pair Shareâ€ can increase study result of C fourth graders students of SDN 80 Pekanbaru on mathematics.Key words: Cooperative Learning Method Type â€œThink Pair Share (TPS), Learning Achievement of Mathematics.